Membraneless Microfluidic Fuel Cell with Silver Electrode Fabricated by Low Temperature Co-fired Ceramic Combined with Photolithography - Seon, Ji-Yun; Joon Yoon, Young (Asian Journal of Chemistry, 2015)
A microfluidic fuel cell fabricated by low temperature co-fired ceramic process was introduced. It was an alkaline fuel cell and produced the electric power via electrochemical reaction using a diverse fuel and an oxidant solution. Highly conductive silver was used for an electrode as a less expensive and non-precious metal catalyst. The fuel is 1 M KOH and the oxidant is 1 M H2SO4 without any electrolytes. In particular, by adding oxygen into the both of solutions by bubbling system, a higher open circuit potential was observed compared to that of normal condition. To enhance the efficiency of potential voltage of single-channel fuel cell, a noble design for dual-channel was employed in a microfluidic fuel cell. After optimizing the flow rates of fuel and oxidant, the open circuit potentials of single-channel and dual-channel microfluidic fuel cell were about 0.25 V and 0.65 V, respectively.